(3QSGdI aj NHQ JCdja GdCdMGfs - (3CHh YeQ GdcfOj , CHh jYbhH Hf eMeO Hf ESMGb GdcfOj, GdcfOj,J (B355 (3g` s
(3ChdgG (B:s
(3bO HjffG Cf aVd GdPi HGdNeSI Ydi GdPi HGdCQHYI (B: s
(3BNQgG (B:s
(3hgPG ajeG SCdJ cGf , caGc Gddg Gdege ef CeQ OfjGc hCNQGc s
(3fbdkG Yf CUd ecJhH SfI (B621 (3HeOjfI OeTbs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B148 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B142s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B209 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B55 s
Keywords: (3GdehSjbi hGdZfGAs